Track of GPS Drifter ICBM-BASS 2022-14 near Helgoland - Deyle, Lisa; Meyerjürgens, Jens; Meyer-Hagg, Lars; Wurl, Oliver; Badewien, Thomas Henry (In: Deyle, L et al. (2024): North Sea drifter data September 2022 near Helogland [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.971303, 2024)
Drifter_North_Sea_ICBM_BASS_2022a is a dataset containing Lagrangian high resolution surface drifter data from two clusters deployed on 21-Sep-2022 (10 drifters) and 22-Sep-2022 (11 drifters) in the North Sea (near Helgoland), subjected to a uniform processing and quality control method and interpolated to five minute resolution. The drifters were 0.5 m in height with a subsurface drogue that was directly to the housing. The drag area ratio of the deployed configuration is R=25.6. The drifter deployments were carried out from the RV Senckenberg in the framework of the DFG Research Unit Bass (grant no. 451574234) to track the pathways of surface currents and the circulation and ocean fronts.
Keywords: BASS; Helgoland; Lagrangian data; North Sea; submesoscale; Surface currents; Surface drifters; trajectories